Electrical Stimulation for Lower Urinary Tract Dysfunction in People with Multiple Sclerosis: A Systematic Review - Sedighimehr, Najmeh; Dehghan Manshadi, Farideh (Journal of Clinical Physiotherapy Research, 2018)
Introduction: Lower urinary tract dysfunction (LUTD) is highly prevalent in patients with multiple sclerosis (MS) who suffer from some degrees of voiding dysfunction and/or urinary incontinence (UI), six to eight years after the initial diagnosis of MS. Electrostimulation is an established therapeutic option for neurogenic LUTD. This study aimed to investigate the efficacy of various types of electrical stimulation (ES) used for LUTD in MS patients. Materials and Methods: A systematic review of English-language articles was carried out in PEDro, PubMed, Science Direct, and Google Scholar databases between 1980 and 2017 using the following keywords: multiple sclerosis, electrical stimulation, LUTD, and neurogenic bladder. All the titles and abstracts were checked. Thereafter, full-text copies were obtained in cases where the studies had possible relevance. We carried out a background search by examining reference lists of all obtained articles. Ten treatment studies were identified in the search process. Results: Out of 10 articles, four were about the effects of percutaneous tibial nerve stimulation (PTNS) on LUTD. In three studies, neuromuscular ES, and in one study, interferential current was used. One study surveyed the effect of ES on the dorsal penile or clitoral nerve, and another studied the effect of ES on sacral dermatomes with regard to urinary symptoms. Also, three studies surveyed the effect of ES and its combination with pelvic floor muscle (PFM) training. Conclusion: This review showed that various types of non-invasive ES used for neurogenic LUTD in patients with MS for suppressing detrusor overactivity have also improved bladder compliance. Patients with MS require daily home stimulation treatments. Also, a combination of ES with PFM training is effective in reducing the symptoms of LUTD in MS patients. Keywords: Electrical Neuromodulation, Lower Urinary Tract Dysfunction, Multiple Sclerosis, Neurogenic Bladder